1992
DOI: 10.1080/02626669209492573
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of turbidity with Indian Remote Sensing Satellite-1A data

Abstract: Indian Remote Sensing Satellite-1A Linear Imaging Self Scanning System (IRS-1A-LISS-I) multispectral digital data acquired over the Tawa reservoir region have been analysed to evaluate the turbidity in the surface water. Tawa reservoir water samples were collected on 20 October 1988 concurrent with an IRS-1A overpass. The turbidity was measured at each sampling point in the field with a nephelometer. Reservoir water samples were analysed for total suspended matter, grain size and mineralogy. IRS-1A-LISS-I comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Hence, many studies estimated the turbidity using the remote sensing approach of Landsat TM-bands (Chebud et al, 2012;Song et al, 2011;Zhao et al, 2011), AVHRR (Woodruff et al, 1999;Aguirre-Gomez, 2000), and MODIS bands . The and NIR (wavelength=772-898 nm) bands of Landsat (Bustamante et al, 2009;Brezonik, 2005), red band of LISS-I (wavelength=620-680 nm) (Choubey, 1992), and MODIS band of wavelength 645 nm are found to be strongly correlated with the turbidity concentration.…”
Section: Introductionmentioning
confidence: 94%
“…Hence, many studies estimated the turbidity using the remote sensing approach of Landsat TM-bands (Chebud et al, 2012;Song et al, 2011;Zhao et al, 2011), AVHRR (Woodruff et al, 1999;Aguirre-Gomez, 2000), and MODIS bands . The and NIR (wavelength=772-898 nm) bands of Landsat (Bustamante et al, 2009;Brezonik, 2005), red band of LISS-I (wavelength=620-680 nm) (Choubey, 1992), and MODIS band of wavelength 645 nm are found to be strongly correlated with the turbidity concentration.…”
Section: Introductionmentioning
confidence: 94%
“…Along with chl‐ a , they have also recommended parameters such as Secchi disk depth or turbidity, two popularly measured water clarity indicators, as proxies for cyanoHABs (Chorus & Welker, 2021). Turbidity has been measured successfully through satellite remote sensing for decades (Choubey, 1992; Dogliotti et al., 2015; Moore, 1980; Nechad et al., 2009). While this study only focused on chl‐ a and CIs as proxies, future research could also investigate the utility of SRS‐based turbidity for recreational alerts, and potentially a combined alert system that leverages both SRS‐based chl‐ a and turbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing (RS) is a powerful tool that has been applied to regional water quality monitoring and assessment (Chopra et al 2001;Choubey 1992;Kloiber et al 2002;Nelson et al 2003;Olmanson et al 2002a, b). Studies have demonstrated reliable relationships between water quality parameters, such as total phosphorus, total nitrogen, dissolved oxygen, pH, salinity, Secchi depth, sodium and potassium, and radiance data from the satellites (Alparslan et al 2007;Dewidar and Khedr 2001;Fuller et al 2002a, b).…”
Section: Introductionmentioning
confidence: 99%